Student Career Choices before and during Quarantine Measures - Panina, Svetlana Viktorovna (2020)
Nowadays, in terms of the COVID-19 pandemic, there is a dramatic transformation of the professions in demand and labor market preferences. In this regard, universities need to review and pay special attention to young people’s professional development taking into account new conditions. In February 2020, before quarantine in the Russian Federation, the authors of the present research conducted a survey in order to study the students’ career preferences. The survey involved 616 students of Bachelor’s and Master’s programs of M. K. Ammosov North-Eastern Federal University (“My professional career”), 78 students of the Arctic State Agrotechnological University (“Labor values of youth”), 29 students of the Arctic State Institute of Culture and Arts (“Me and my professional career”). The results showed that the students consider career development as an opportunity to realize their material goals, to combine professional and personal interests, and to set up their own business. In addition, during a quarantine measures due to the COVID 19 pandemic in May 2020, an express survey of 437 students was conducted. The results of the survey showed that some students have changed their attitude to their future career, i.e., they wanted to get advanced professional education, improve their digital skills to make it easier to adapt for remote work. Some students expressed their thoughts regarding future employment, i.e., a budget organization or the sphere of small and medium businesses. The authors concluded that university programs for future specialists’ training should take into account students’ career preferences, desires, professional intentions and attitudes.